The amazing stories of Philippine psychic surgeons - Licauco, Jaime T. 1940- (Mandaluyong City Anvil Publishing, 2013)
Stories about psychic surgeons and healing practices in the Philippines.
Previous edition with title: The magicians of God : the amazing stories of Philippine faith healers.
Includes bibliographical references (page 180).
In English.
Keywords: Psychic surgery -- Philippines; Mental healing -- Philippines; Healers -- Philippines